2003
DOI: 10.1164/rccm.200212-1543oc
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Severe Aspiration Pneumonia in Institutionalized Elderly

Abstract: We sought to investigate prospectively the microbial etiology and prognostic indicators of 95 institutionalized elders with severe aspiration pneumonia, and to investigate its relation to oral hygiene in using quantitative bronchial sampling. Data collection included demographic information, Activity of Daily Living, Plaque Index, antimicrobial therapy, and outcome. Out of the 67 pathogens identified, Gram-negative enteric bacilli were the predominant organisms isolated (49%), followed by anaerobic bacteria (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
2
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(190 citation statements)
references
References 26 publications
8
170
2
10
Order By: Relevance
“…9 Elsolh and Pietrantoni (2003) found dyspnea, fever, and delirium in the majority of patients in their study. 1 In present study all the patients had reduced consciousness. Stroke was found in 32 (64%) patients, encephalitis was found in 8 (16%) patients, hepatic encephalopathy was found in 8 (16%) patients and 2 patients had uremic encephalopathy.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…9 Elsolh and Pietrantoni (2003) found dyspnea, fever, and delirium in the majority of patients in their study. 1 In present study all the patients had reduced consciousness. Stroke was found in 32 (64%) patients, encephalitis was found in 8 (16%) patients, hepatic encephalopathy was found in 8 (16%) patients and 2 patients had uremic encephalopathy.…”
Section: Discussionsupporting
confidence: 55%
“…Approximately 10% of patients who are hospitalized due to altered consciousness or drug overdose will have aspiration pneumonia. 1 Aspiration pneumonia is more common in extremely young and old patients and in males than females. 2 The mortality rate of aspiration pneumonia is approximately 1% in outpatient setting and upto 25% in those requiring hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Data about microbiological diagnosis of aspiration pneumonia are disparate for the following three reasons: First, several studies enrolled patients relatively late, when complications such as necrotizing pneumonia, lung abscess, or empyema had already occurred; and in these patients, anaerobic organisms were found to be the predominant pathogens isolated alone or with aerobes (10,11), whereas most common pathogens isolated in relatively early enrolled patients with aspiration pneumonia are Streptococcus pneumonia, gram-negative bacilli, anaerobes, and Staphylococcus aureus (12). Second, in many cases, it is impossible to isolate the responsible pathogens.…”
Section: Bacteriology Of Aspiration Pneumonia -Normal Flora Pneumoniaementioning
confidence: 99%
“…nucleatum is the coaggregating partner for P. gingivalis and may be present with P. gingivalis in the oral cavity Kinder and Holt, 1989 . P. gingivalis and F. nucleatum are common isolates from aspiration pneumonia Okuda, 2005;El-Solh et al, 2003 . Our result with these bacterial species demonstrated that the DEPIM method is useful for counting the number of coaggregated bacterial samples better than the culture method data not shown .…”
Section: O M P L I C a T E D I N T E R T W I N I N G O F C H A I N E mentioning
confidence: 99%